Porphyromonas gingivalis-induced periodontitis promotes neuroinflammation and neuronal loss associated with dysfunction of the brain barrier - Jiang, Yiting; Xu, Lina; Zhao, Xuri; Shen, Hui; Qiu, Che; He, Zhiyan; Song, Zhongchen; Zhou, Wei (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundIn our previous study, Porphyromonas gingivalis (P. gingivalis)-induced periodontitis caused cognitive impairment which was associated with abnormal amyloid β (Aβ) metabolite in the brain. The brain barrier is critical in maintaining homeostasis, controlling influx and efflux transport and regulating waste clearance. However, the specific role of the brain barrier in linking periodontitis to cognitive function remains unclear.MethodsA murine model of periodontitis-induced cognitive impairment was constructed via oral topical application of P. gingivalis. Neuroinflammation was observed by detecting the expression of proinflammatory cytokines and glia activation. Western blot (WB), immunohistochemistry (IHC) and immunofluorescence (IF) were used to detect the expression of tau-related molecules and neuronal loss. WB, Evans blue staining and flow cytometry were used to evaluate the blood-brain barrier (BBB) function including the infiltration of P. gingivalis and immune cells, and BBB permeability. The changes of meningeal lymphatic drainage were observed using an in vivo animal imaging system and reverse transcription polymerase chain reaction (RT-PCR). The effect of P. gingivalis on lymphatic endothelial cells (LECs) was further verified using IF and RT-PCR.ResultsP. gingivalis-induced periodontitis exacerbated cognitive impairment by the upregulation of proinflammatory cytokine and glia activation. In the brain of periodontitis mice, p-Akt and p-GSK3β levels were reduced, leading to tau hyperphosphorylation and neuronal loss including cell bodies and neurites. P. gingivalis-induced periodontitis enhanced BBB permeability, promoted P. gingivalis and immune cell infiltration, and downregulated the expression of Occludin and ZO-1. In addition, the meningeal lymphatic drainage was impaired and the mRNA levels of lymphangiogenesis-related factor LYVE1 were decreased in the dura matter of periodontitis mice. After P. gingivalis infection, the inflammatory response was increased, and LYVE1 and ZO1 expression was decreased in LECs.ConclusionsPeriodontitis aggravated neuroinflammation and neuronal loss which was associated with tau hyperphosphorylation. The impaired meningeal lymphatic vessels (MLV) and disrupted BBB affected the brain barrier function, further inhibiting the clearance of pathogenic substances and enhancing immune cell infiltration in periodontitis mice. These results indicated that brain barrier dysfunction may be the link between periodontitis and cognitive impairment.